KISHI MEKTEP JASÍNDAǴÍ BALALARDA OQÍWǴA BOLǴAN QÍZÍǴÍWSHÍLÍǴÍN QÁLIPLESTIRIW - Matkarimova, M. (SCIENCE and SOCIETY, 2018)
The article is devoted to the issues of psychological training of children of junior age for school, the role of a teacher in the teaching process and the basic components of educational activity.